High Voltage LiNi0.5Mn0.3Co0.2O2/Graphite Cell Cycled at 4.6 V with a FEC/HFDEC‐Based Electrolyte. Issue 15 (26th April 2017) - He, Meinan; Su, Chi‐Cheung; Feng, Zhenxing; Zeng, Li; Wu, Tianpin; Bedzyk, Michael J.; Fenter, Paul; Wang, Yan; Zhang, Zhengcheng
Abstract : A high voltage LiNi0.5 Mn0.3 Co0.2 O2 /graphite cell with a fluorinated electrolyte formulation 1.0m LiPF6 fluoroethylene carbonate/bis(2, 2, 2‐trifluoroethyl) carbonate is reported and its electrochemical performance is evaluated at cell voltage of 4.6 V. Comparing with its nonfluorinated electrolyte counterpart, the reported fluorinated one shows much improved Coulombic efficiency and capacity retention when a higher cut‐off voltage (4.6 V) is applied. Scanning electron microscopy/energy dispersive X‐ray spectroscopy and X‐ray photoelectron spectroscopy data clearly demonstrate the superior oxidative stability of the new electrolyte. The structural stability of the bulk cathode materials cycled with different electrolytes is extensively studied by X‐ray absorption near edge structure and X‐ray diffraction. Abstract : A high voltage electrolyte based on fluoroethylene carbonate and bis(2, 2, 2‐trifluoroethyl) carbonate is developed for high voltage LiNi0.5 Mn0.3 Co0.2 O2 /graphite cells cycled between 3.0–4.6 V. The enhanced oxidative stability of the fluorinated electrolyte is examined by electrochemical cycling, microscopy, and electroscopy. The reported electrolyte also passivates the graphite enabling reversible Li + intercalation/deintercalation on the anode side.